Некоторые аспекты производства обогащенных пищевых продуктов - Shegelman I. R., Sukhanov I. V., Vasilyev A. S. (Scientific studies: theory, methodology and practice, 2018)
the production of functional food products is one of the important directions in the development of the food industry, since trends in population demography, consumer welfare, raising the level of education, life expectancy require a full and balanced diet.
Keywords: производство пищевых продуктов; функциональные продукты; production of food products; обогащенные продукты; fortified products; functional products